Businesses blogging and the effects of non-compliance - Mohamed, Duryana (International Foundation for Research and Development, 2015)
Presently, business blogging is gaining increasing on-line popularity. Some bloggers or business owners engage in this form of business for limited periods to test the marketability of their products, while others rely on it as the primary medium for marketing their products and services. Given that commerce is being conducted via blogs, some exploit this medium for fraudulent purposes. In Malaysia, there are legal rules and regulations governing online transactions or electronic commerce. However, to date these have not been updated to include specific provisions for business blogging. The legal issues that arise are whether owners of such commercial blogs should comply with the existing legal framework governing online transactions or electronic commerce and are thus liable to consumers under consumer laws. This paper discusses the above issues by examining the application of existing laws on business blogging and the effects of non-compliance.